Surgical complications in immediate and delayed breast reconstruction: a systematic review and meta-analysis - Matar, Dany Y.; Wu, Mengfan; Haug, Valentin; Orgill, Dennis P.; Panayi, Adriana C. (Journal of plastic, reconstructive & aesthetic surgery, 2022)
Background - Because of improved aesthetic results, immediate breast reconstruction has become the most widely used timing of reconstruction following mastectomy. Many studies report complication rates between immediate and delayed reconstructions at certain medical institutions, but no systematic reviews exist to summarize the literature. This systematic review was conducted to assess the outcomes in women who underwent immediate versus delayed breast reconstruction following mastectomy for breast cancer. - Methods - Cochrane, PubMed, and EMBASE electronic databases were screened, and data were extracted from included studies. The clinical outcomes assessed were surgical complications, length of postoperative hospital stay, and reoperation rate. - Results - A total of 30 studies met the inclusion criteria for the review and provided enough data to be included in the meta-analysis (14,034 patients). Women receiving immediate breast reconstruction were significantly more likely to experience surgical complications (OR 1.30, 95% CI 1.03, 1.65; p = 0.03). Sensitivity analysis showed that women receiving immediate reconstruction were also more likely to experience infection (OR 1.41, 95% 1.04, 1.92; p = 0.03) and hematoma/seroma (OR 2.01, 95% CI 1.27-3.17; p = 0.003). Furthermore, a separate sensitivity analysis showed no significant differences in reported outcomes when comparing studies whose patient cohorts received post-mastectomy radiation therapy (PMRT). - Conclusions - This study provides evidence that immediate breast reconstruction generally increases the risk of complications in comparison with delayed reconstruction. Additional prospective and observational studies are needed to determine the role of PMRT and reconstruction surgical technique in the incidence of complications between immediate and delayed reconstructions.